Assessing Saudi Paramedics Preparedness for Mass Casualty Incidents and Disasters: A Descriptive Quantitative Study - Alazmy, Waleed (Asian Journal of Pharmaceutics (AJP), 2025)
This study investigates the preparedness of Saudi paramedics for mass casualty incidents (MCIs) and disasters. Methods: A cross-sectional study-using questionnaire was conducted among Saudi paramedics. A total of 480 ambulance stations of the Saudi Red Crescent Authority (SRCA), located around its 13 administrative regions (SRCA, 2019) were included. A response rate of 94.8% (n = 455) through a convenience sampling approach was obtained. Three factors were assessed: Roles and responsibilities, preparedness, and barriers to responding effectively. Results: Participants reported a limited understanding of their roles and responsibilities, while the majority of participants reported a moderate knowledge of preparedness. Different barriers show a moderate impact on preparedness ranging from (mean [M] = 6.65, Standard deviation [SD] 2) to (M = 7.87, SD = 2.54). Conclusion: The present study recommends the improvement of paramedics’ preparedness for MCIs and disaster through mock drills, training, and a curriculum for preparedness. Leadership skills also need improvement for paramedics to enhance their preparedness for MCIs and disasters